BASICS OF PROFESSIONAL AND COMMUNICATIVE COMPETENCE OF AIR TRAFFIC CONTROLLERS IN THE USA - Скіпальська, Олена (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
This paper explores the fundamentals of professional and communicative competence required for air traffic controllers (ATCOs). Purpose. The article examines the definitions provided by international aviation authorities, the essential elements that make up these competencies, the techniques used for their training and evaluation, and their overall effects on aviation safety and operational effectiveness. It also addresses the difficulties encountered in maintaining these standards and discusses upcoming developments influencing the skills and expertise needed by ATCOs. Methods. The document references definitions and standards from organizations like the International Civil Aviation Organizations (ICAO) and the Federal Aviation Administration (FAA). It also analyses various documents and publications related to air traffic control, training, and language proficiency. Results. The paper emphasizes that professional competence provides the fundamental knowledge and skills for air traffic control, while communicative competence enables ATCOs to apply this knowledge effectively in real-time interactions, ensuring the safety and efficiency of air travel. The ICAO’s framework and FAA’s requirements are discussed in details. Conclusion. The professional and communicative competence of air traffic controllers is essential for the safe and efficient flow of air traffic. Both competencies are developed through careful training and ongoing evaluation to ensure that ATCOs can effectively manage the difficulties of air traffic control and uphold safety.